The mechanism and application of traditional Chinese medicine extracts in the treatment of lung cancer and other lung-related diseases - He, Zhenglin; Wang, Yihan; Han, Liang; Hu, Yue; Cong, Xianling (Frontiers in Pharmacology, 2023)
Lung cancer stands as one of the most prevalent malignancies worldwide, bearing the highest morbidity and mortality rates among all malignant tumors. The treatment of lung cancer primarily encompasses surgical procedures, radiotherapy, and chemotherapy, which are fraught with significant side effects, unfavorable prognoses, and a heightened risk of metastasis and relapse.Although targeted therapy and immunotherapy have gradually gained prominence in lung cancer treatment, diversifying the array of available methods, the overall recovery and survival rates for lung cancer patients remain suboptimal. Presently, with a holistic approach and a focus on syndrome differentiation and treatment, Traditional Chinese Medicine (TCM) has emerged as a pivotal player in the prognosis of cancer patients. TCM possesses characteristics such as targeting multiple aspects, addressing a wide range of concerns, and minimizing toxic side effects. Research demonstrates that Traditional Chinese Medicine can significantly contribute to the treatment or serve as an adjunct to chemotherapy for lung cancer and other lung-related diseases. This is achieved through mechanisms like inhibiting tumor cell proliferation, inducing tumor cell apoptosis, suppressing tumor angiogenesis, influencing the cellular microenvironment, regulating immune system function, impacting signal transduction pathways, and reversing multidrug resistance in tumor cells. In this article, we offer an overview of the advancements in research concerning Traditional Chinese Medicine extracts for the treatment or adjunctive chemotherapy of lung cancer and other lungrelated conditions. Furthermore, we delve into the challenges that Traditional Chinese Medicine extracts face in lung cancer treatment, laying the foundation for the development of diagnostic, prognostic, and therapeutic targets.